Effects of sodium hydroxide in a selective chemical treatment of Peruvian peloids - Cerón Loayza, M. L. (2010)
The main purpose of this work is to apply the NaOH treatment to the silt and clay peloids in order to selectively concentrate iron oxides (1) by dissolving and removing phyllosilicates, for a better identification of oxides in the mineralogical composition of samples. For the mineralogical characterization of the samples that contain iron, especially for those that show magnetic ordering, transmission Mossbauer spectroscopy (TMS) was applied using the 14.4 KeV resonant nuclear transition in the 57Fe isotope; which allowed the detection of sesquioxides and other minerals that contain iron. For the identification of crystalline phases we use X ray diffractometry (XRD) technique. The NaOH treatment was applied sequentially to each sample and monitored by TMS and XRD. The results by TMS show paramagnetic doublets and the presence of partially oxidized magnetite. The XRD results of the samples without treatment show the presence of quartz and phyllosilicates such as vermiculite and halloysite. After selective chemical treatment the phyllosilicates were eliminated almost in their totality whereas the main (311) reflection belonging to iron oxide spinel was evident. As a general trend, the NaOH treatment was significantly effective in concentrating iron oxide minerals in the studied peloids. The applied analytical techniques corroborate these results.